Integral manifolds of impulsive differential equations. (1992) - Bainov, D. D.; Kostadinov, S. I.; Van Minh, N.; Thai, N. Hong; Zabreiko, P. P.
Abstract : The present paper is concerned with the existence of integral manifolds of impulsive differential equations as t → + ∞ . Under the assumption of exponential trichotomy on the linear part of the right-hand side of the equation, it is proved that if the nonlinear perturbation is small enough, then there exist integral manifolds as t → + ∞ for the perturbed equations.